2018
DOI: 10.5194/essd-10-1829-2018
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Sea climatic indices: monitoring long-term variability and climate changes

Abstract: Abstract. We present a new product composed of a set of thermohaline climatic indices from 1950 to 2015 for the Mediterranean Sea such as decadal temperature and salinity anomalies, their mean values over selected depths, decadal ocean heat and salt content anomalies at selected depth layers as well as their long time series. It is produced from a new high-resolution climatology of temperature and salinity on a 1∕8∘ regular grid based on historical high-quality in situ observations. Ocean heat and salt content… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Indeed, it has been shown that oceans acted as sinks for more than 90% of the extra energy balance associated with climate change between 1971 and 2010 [7], thus raising SST in the global oceans. Regarding the Mediterranean region, observations have permitted us to calculate an increasing trend in OHC of 0.8 ± 0.1 W/m 2 in the 0-700 m layer [8], with an increasing trend after 2005 [9]. From a long SST series recorded at a measuring site in the western Mediterranean basin, [10] also found a warming trend for both SST and sea temperature at different depths.…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, it has been shown that oceans acted as sinks for more than 90% of the extra energy balance associated with climate change between 1971 and 2010 [7], thus raising SST in the global oceans. Regarding the Mediterranean region, observations have permitted us to calculate an increasing trend in OHC of 0.8 ± 0.1 W/m 2 in the 0-700 m layer [8], with an increasing trend after 2005 [9]. From a long SST series recorded at a measuring site in the western Mediterranean basin, [10] also found a warming trend for both SST and sea temperature at different depths.…”
Section: Introductionmentioning
confidence: 94%
“…4b). The most recent reanalyses of the climatic trends in salinity show an increase in the area at different depths (Iona et al 2018), but the sources of uncertainty associated with these projections (including river discharges) suggest that they should be interpreted with caution. The projections of surface chlorophyll-a presented even higher uncertainties than salinity for our study area.…”
Section: Biogeochemical Projection Modelmentioning
confidence: 99%
“…The seasonal cycle has been removed. a result of the direct forcing from the atmosphere associated with the hemispheric patterns that are known to influence central Mediterranean temperatures and precipitation (like the East Atlantic pattern; Ionita et al, 2015;Scorzini et al, 2018). The bottom variability of residual salinity is likely largely due to the advection of salt from the southeast through the Adriatic-Ionian thermohaline circulation (Orlić et al, 2006).…”
Section: Interannual Variabilitymentioning
confidence: 99%